2022
DOI: 10.1016/j.jaclp.2021.07.010
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Electroconvulsive Therapy in Neuropsychiatric Complications of Coronavirus Disease 2019: A Systematic Literature Review and Case Report

Abstract: Objective This study reports on the use of electroconvulsive therapy (ECT) in neuropsychiatric symptoms (NPS) associated with COVID-19. Methods A review of the literature pertaining to the use of ECT in COVID-19 patients with NPS was performed through PubMed, PsycINFO, and MEDLINE. Search terms included “Electroconvulsive Therapy” and “ECT,” combined with “COVID-19” and “SARS-COV-2.” Additionally, we present a case in which ECT was used to achieve complete remission in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Finally, 18 articles did not include individual level data and 7 articles were available as abstracts only. A total of 40 articles met inclusion criteria, comprising 48 individual patients from 17 countries ( Table 1 ) [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ]. All but a single study [ 54 ] were in English and 20 (42%) cases were reported in the United States, where the largest proportion of these cases were documented.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 18 articles did not include individual level data and 7 articles were available as abstracts only. A total of 40 articles met inclusion criteria, comprising 48 individual patients from 17 countries ( Table 1 ) [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ]. All but a single study [ 54 ] were in English and 20 (42%) cases were reported in the United States, where the largest proportion of these cases were documented.…”
Section: Resultsmentioning
confidence: 99%
“… Reported Dx: Psychosis associated with probable encephalitis associated with SARS-CoV-2 DSM-5 Dx: Psychotic disorder due to autoimmune encephalitis History of borderline intellectual functioning and “thinking with a high level of pervious mysticism.” Receipt of ampicillin/sulbactam before onset of symptoms. Austgen et al, 2021 [ 29 ] 52, F, US Insomnia and anxiety after receiving steroids for “mild COVID-19,” which progressed to paranoia and depression over 1 month requiring hospitalization. Again hospitalized 48 h later for suicidal thoughts, psychomotor slowing, paranoia and catatonia.…”
Section: Resultsmentioning
confidence: 99%
“…Patients not treated with APs suffered either from a defined organic brain disorder (Panariello et al, 2020a;Alvarez-Cisneros et al, 2021;Elfil et al, 2021;McAlpine et al, 2021), from catatonia (Caan et al, 2020;Zain et al, 2021) or were thought to have a psychosis due to an offending drug, which was then withdrawn. Three patients were treated with electroconvulsive therapy (ECT) (Chacko et al, 2020;Vepa et al, 2020;Austgen et al, 2021). The mean dosage of antipsychotics at discharge was 3.4 mg risperidone equivalents.…”
Section: Patients With Infectionmentioning
confidence: 99%
“… 37 , 38 Of note, there was one case in which ECT was effective for neuropsychiatric symptoms in COVID-19. 39 All these reports reaffirm the importance of ECT. We must continue to provide ECT to as many eligible patients as possible with appropriate infection control measures.…”
Section: Discussionmentioning
confidence: 83%